Nationwide Surveillance of Novel Oxazolidinone Resistance Gene optrA in Enterococcus Isolates in China from 2004 to 2014 - Cui, Lanqing; Wang, Yang; Lv, Yuan; Wang, Shan; Song, Yunjia; Li, Yun; Liu, Jian; Xue, Feng; Yang, Weiwei; Zhang, Jia (Antimicrobial agents and chemotherapy, 2016)
A total of 2,201 nonduplicate enterococcal isolates collected from 29 hospitals in 23 cities in China between 2004 and 2014 were screened for the oxazolidinone resistance gene optrA; 45 isolates (2.0%) were optrA positive with 11 OptrA variants identified. The positive rate of optrA increased from 0.4% to 3.9% during the 10-year surveillance period. Pulsed-field gel electrophoresis (PFGE) and multilocus sequence type (MLST) analysis revealed that 37 optrA-positive Enterococcus faecalis isolates clustered into 25 PFGE patterns and 21 sequence types, while 6 Enterococcus faecium isolates represented 6 PFGE patterns and 6 sequence types. The present study underscores the importance of routine and persistent monitoring of oxazolidinone resistance and optrA gene.